Solid battery
The solid-state battery's three-layer current collector structure with resin and metal layers, and mixed components, addresses adhesion and conductivity issues, resulting in improved performance.
Patent Information
- Application Number
- JP2023110340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional solid-state batteries face issues with low adhesion between the current collector and the active material layer, and low electronic conductivity, particularly in current collectors made of ceramic foil or metal foil, and resin layers.
A solid-state battery design featuring a three-layer structure for both current collectors, comprising a resin layer and a metal layer, with the resin layer on the active material layer side, and a mixed component layer between the current collector and the active material layer to enhance adhesion and conductivity.
The design achieves improved adhesion and electronic conductivity between the current collector and the active material layer, enhancing the overall performance of the solid-state battery.
Smart Images

Figure 2025008298000002 
Figure 2025008298000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to solid-state batteries. [Background technology]
[0002] 2. Description of the Related Art In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (EVs), hybrid vehicles (HVs), and plug-in hybrid vehicles (PHVs), among others.
[0003] Secondary batteries use electrolytes that contain flammable organic solvents, so they require the installation of safety devices to suppress temperature rises in the event of a short circuit, as well as improvements to the structure and materials to prevent short circuits. In contrast, solid-state batteries, which use solid electrolyte layers to solidify the materials, do not use flammable organic solvents inside the battery, so safety devices can be simplified and they are thought to be superior in terms of manufacturing costs and productivity. Conventional current collectors for solid-state batteries have a single-layer structure made of ceramic foil or metal foil, or a laminate containing ceramic foil and metal foil. However, conventional current collectors made of ceramic foil or metal foil have low adhesion between the current collector and the active material layer (i.e., the active material layer), and the current collector may peel off from the active material layer. In response to this, in recent years, development has been underway on resin layers containing resin as current collectors for solid-state batteries from the viewpoints of weight reduction, cost reduction, etc. (For example, Patent Document 1). However, resin layers tend to have lower electronic conductivity than current collectors made of ceramic foil or metal foil. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-097018 Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, in a conventional solid-state battery having only one of a current collector made of a ceramic foil or metal foil and a resin layer, the adhesion between the current collector and the active material layer is low, or the electronic conductivity is low. In view of the above circumstances, an object of the present disclosure is to provide a solid-state battery that is excellent in both adhesion between a current collector and an active material layer and in electronic conductivity. [Means for solving the problem]
[0006] Means for solving the above problems include the following means. <1> a first current collector including a first resin layer containing a resin and a conductive material and a first metal layer; a first active material layer; solid electrolyte layer, A second active material layer, and a second current collector including a second resin layer containing a resin and a conductive material and a second metal layer; are layered in this order, a first resin layer provided on the first current collector on a side of the first active material layer, and a second resin layer provided on the second current collector on a side of the second active material layer. <2> a first intermediate layer between the first current collector and the first active material layer, in which at least one component contained in the first active material layer and at least one component contained in the resin layer are mixed; The present invention further comprises a second intermediate layer between the second current collector and the second active material layer, the second intermediate layer including at least one component contained in the second active material layer and at least one component contained in the resin layer. <1> The solid-state battery according to claim 1, <3> the first current collector has a three-layer structure in which the first resin layer, the first metal layer, and the first resin layer are laminated in this order from the first active material layer side, the second current collector has a three-layer structure in which the second resin layer, the second metal layer, and the second resin layer are laminated in this order from the second active material layer side; <1> or <2> The solid-state battery according to claim 1, Effect of the Invention
[0007] According to the present disclosure, a solid-state battery is provided that is excellent in both adhesion between a current collector and an active material layer and in electronic conductivity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are intended to illustrate the embodiment, and are not intended to limit the scope of the present disclosure.
[0010] In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In the present disclosure, in the ranges of numerical values described stepwise, the upper limit or lower limit of one numerical range may be replaced with the upper limit or lower limit of another numerical range of numerical values described stepwise. In addition, in the ranges of numerical values described in the present disclosure, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the description of groups (atomic groups) in the present disclosure, a description without specifying whether substituted or unsubstituted includes both those containing no substituents and those containing a substituent. In this disclosure, the term "layer" includes cases where the layer is formed over the entire area when the area in which the layer exists is observed, as well as cases where the layer is formed over only a portion of the area. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.
[0011] -Solid battery- The solid-state battery according to the present disclosure is a solid-state battery in which a first current collector including a first resin layer containing a resin and a conductive material and a first metal layer, a first active material layer, a solid electrolyte layer, a second active material layer, and a second current collector including a second resin layer containing a resin and a conductive material and a second metal layer are laminated in this order, with the first resin layer being provided on the first active material layer side of the first current collector, and the second resin layer being provided on the second active material layer side of the second current collector.
[0012] According to the present disclosure, both the adhesion between the current collector and the active material layer and electronic conductivity are excellent. The mechanism by which this occurs is not entirely clear, but is presumed to be as follows. The solid-state battery according to the present disclosure has both a metal foil and a resin layer as a current collector, and the resin layer is provided on the active material layer side, and therefore it is believed that the metal layer provides excellent electronic conductivity, and the resin layer provides excellent adhesion between the active material layer and the current collector.
[0013] The solid-state battery of the present disclosure includes a so-called all-solid-state battery using a solid electrolyte as an electrolyte, and the solid electrolyte may contain an electrolytic solution in an amount of less than 10 mass% based on the total amount of the electrolyte. The solid electrolyte may be a composite solid electrolyte containing an inorganic solid electrolyte and a polymer electrolyte.
[0014] An example of a solid-state battery according to the present disclosure will be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. The solid-state battery shown in Fig. 1 includes a negative electrode including a negative electrode current collector 113 (first current collector) and a negative electrode active material layer A (first active material layer), a solid electrolyte layer B, and a positive electrode including a positive electrode current collector 115 (second current collector) and a positive electrode active material layer C (second active material layer). The negative electrode current collector 113 (first current collector) is a three-layer laminate in which a first resin layer, a first metal layer, and a first resin layer are laminated in this order from the negative electrode active material layer A (first active material layer) side. The positive electrode current collector 115 (second current collector) is a three-layer laminate in which a second resin layer, a second metal layer, and a second resin layer are laminated in this order from the positive electrode active material layer C (second active material layer) side. The negative electrode active material layer A includes a negative electrode active material 101, a conductive assistant 105, a binder 109, and a solid electrolyte 102. The positive electrode active material layer C includes a positive electrode active material 103, a conductive assistant 107, a binder 111, and a solid electrolyte 102.
[0015] When a set of a positive electrode, a solid electrolyte layer, and a negative electrode is defined as a power generation unit, the solid-state battery may have only one power generation unit or may have two or more power generation units. When the solid-state battery has two or more power generation units, the power generation units may be connected in series or in parallel.
[0016] In the solid-state battery, the stacking end faces (i.e., side faces) of the stacking structure of the positive electrode / solid electrolyte layer / negative electrode may be sealed with a sealant such as resin. The negative electrode current collector 113 and the positive electrode current collector 115 may have a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on the outer circumferential surface. The shape of the solid-state battery is not particularly limited, and may be, for example, a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.
[0017] Hereinafter, matters common to both the first current collector and the second current collector will be collectively referred to simply as "current collector". The first current collector and the second current collector may have the same or different layer configurations and component compositions. For example, when the type and amount of resin contained in the material, the type and amount of conductive material contained in the material, etc. are different, the first current collector and the second current collector are considered to have different component compositions. Hereinafter, matters common to both the first active material layer and the second active material layer will be collectively referred to simply as "active material layer". The first active material layer and the second active material layer may have the same or different component compositions. For example, when the type and amount of active material contained in the material, the type and amount of binder, etc. are different, the first active material layer and the second active material layer are considered to have different component compositions. Hereinafter, matters common to both the first resin layer and the second resin layer will be collectively referred to simply as "resin layer". The first resin layer and the second resin layer may have the same or different component compositions. For example, when the type and amount of resin contained in the material, the type and amount of conductive material contained in the material, etc. are different, the first resin layer and the second resin layer are considered to have different component compositions. Hereinafter, matters common to both the first metal layer and the second metal layer will be collectively referred to simply as "metal layer". The first metal layer and the second metal layer may have the same or different component compositions. For example, when the types of metals constituting the metal foil are different, the first metal layer and the second metal layer are considered to have different component compositions.
[0018] Each layer structure will be described in detail below.
[0019] [Current collector] The current collector includes a resin layer containing a resin and a conductive material, and a metal layer, with the resin layer being provided on the active material layer side.
[0020] The current collector may be a laminate of two or more layers including a resin layer and a metal layer, and is preferably a laminate of two to four layers, and more preferably a laminate of two to three layers.
[0021] The current collector preferably has a three-layer structure in which, for example, a resin layer, a metal layer, and a resin layer are laminated in this order from the active material layer side. That is, the first current collector preferably has a three-layer structure in which, from the first active material layer side, a first resin layer, a first metal layer, and a first resin layer are laminated in this order, and the second current collector preferably has a three-layer structure in which, from the second active material layer side, a second resin layer, a second metal layer, and a second resin layer are laminated in this order.
[0022] Resin layer The resin layer contains a resin and a conductive material. Examples of the resin include known thermoplastic resins such as poly(meth)acrylic acid, polymethyl(meth)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and halogenated vinyl resin; thermosetting resins such as epoxy resin, vinyl ester resin, unsaturated polyester resin, phenol resin, and melamine resin; and known conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, and polyoxadiazole. The resin may be used alone or in combination of two or more kinds. Among the above, from the viewpoint of achieving better adhesion between the current collector and the active material layer, the resin preferably contains at least one of a thermoplastic resin and a conductive polymer, more preferably contains a thermoplastic resin, and even more preferably contains one type of resin selected from the group consisting of polymethyl(meth)acrylate, poly(meth)acrylic acid, and polyacrylonitrile.
[0023] In the present disclosure, the term "(meth)acrylic acid" is a concept that encompasses both acrylic acid and methacrylic acid, and the term "(meth)acrylate" is a concept that encompasses both acrylate and methacrylate.
[0024] The resin may be a crystalline resin, an amorphous resin, or a mixture of both, and from the viewpoint of further suppressing the warping of the active material layer from the resin layer, an amorphous resin is preferable. The "crystalline" resin refers to the presence of an endothermic peak with a half-width of 10°C or less when measured at a heating rate of 10 (°C / min) in differential scanning calorimetry (DSC measurement). On the other hand, the "amorphous" resin refers to the half-width exceeding 10°C, or the absence of a clear endothermic peak.
[0025] The softening temperature of the resin varies depending on the type of resin, but from the viewpoint of, for example, the strength of the resin layer and the suppression of deterioration of the active material, the softening temperature of the resin is preferably equal to or lower than the crystallization temperature of the solid electrolyte contained in the solid electrolyte layer described later. The softening temperature of the resin is determined from a DSC curve obtained by differential scanning calorimetry (DSC).
[0026] Examples of the conductive material include carbon materials, conductive polymers, and metal particles. Examples of carbon materials include particulate carbon materials, fibrous carbon materials, etc. Examples of particulate carbon materials include graphite, acetylene black (AB), Ketjen black (KB), etc. Examples of fibrous carbon materials include carbon nanotubes (CNT), carbon nanofibers (CNF), vapor grown carbon fibers (VGCF), etc. Examples of the conductive polymer include polythiophene, polyacetylene, polyparaphenylene, and polyisothianaphthene. Metal particles include nickel, copper, iron, stainless steel, and the like particles. Among the above, from the viewpoint of improving the adhesion between the current collector and the active material layer and improving the electronic conductivity of the current collector, the conductive material preferably contains at least one of a carbon material and a fibrous carbon material, and more preferably contains at least one of acetylene black (AB) and vapor-grown carbon fiber (VGCF).
[0027] From the viewpoint of improving the adhesion between the current collector and the active material layer and improving the electronic conductivity of the current collector, the content of the conductive material is preferably from 10 mass % to 50 mass % inclusive, more preferably from 15 mass % to 43 mass % inclusive, and even more preferably from 15 mass % to 35 mass % inclusive, relative to the total solid content of the resin layer.
[0028] The resin layer may further contain other materials in addition to the resin and the conductive material, such as a binder, a "dispersant" that improves the dispersibility of the conductive assistant in the slurry, and a "wetting agent" that improves the wettability between the foil and the slurry.
[0029] From the viewpoint of improving the electronic conductivity of the current collector, the resin layer is made of a material having a linear expansion coefficient of 100×10 -6 ppm / K or more 500×10 -6 It is preferable that the concentration is less than 200×10 ppm / K. -6 ppm / K or more 430×10 -6 More preferably, it is 230×10 ppm / K or less. -6 ppm / K or more 350×10 -6 It is more preferable that the coefficient of linear expansion is not more than ppm / K. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993.
[0030] The method for adjusting the linear expansion coefficient of the resin layer to fall within the above range is not particularly limited, and examples thereof include a method in which the resin in the resin layer is one of the above-mentioned suitable resins.
[0031] The thickness of the resin layer is not particularly limited, but from the viewpoint of, for example, the energy density of the battery, the thinner the better. For example, from the viewpoint of improving the adhesion between the current collector and the active material layer, the thickness of the resin layer is preferably 5 μm or more and 80 μm or less, more preferably 10 μm or more and 50 μm or less, and even more preferably 10 μm or more and 30 μm or less.
[0032] The thickness of the resin layer is determined by observing a cross section of the resin layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and measuring the thickness at any ten points, and averaging the thicknesses.
[0033] The method for forming the resin layer is not particularly limited, but examples thereof include a method in which, when the resin is thermoplastic, a coating liquid containing the resin and a conductive material is applied, dried, and molded; and, when the resin is thermosetting, a method in which raw materials such as a resin precursor or a monomer and a conductive material are placed in a mold and heated to solidify.
[0034] From the viewpoint of improving the adhesion between the current collector and the active material layer, the resin layer, i.e., the first current collector and the second current collector, preferably has a compressive strength of 450 MPa or less, more preferably 400 MPa or less, and even more preferably 100 MPa or more and 400 MPa or less. The compressive strength of a resin current collector is determined as follows. A test specimen is prepared by stacking multiple resin current collectors. When this test specimen is compressed in a uniaxial press, the compressive strength at which plastic deformation begins (i.e., 5% deformation) is taken as the compressive strength. If the test specimen breaks before 5% deformation, the maximum strength until breakage is taken as the compressive strength.
[0035] ·Metal layer The metal layer may be made of a known material used as a metal foil, such as aluminum foil, nickel foil, titanium foil, copper foil, etc.
[0036] The thickness of the metal layer is not particularly limited, but from the viewpoint of, for example, achieving better electronic conductivity and better adhesion to the active material layer, it is preferably 1 μm or more and 100 μm or less, more preferably 3 μm or more and 20 μm or less, and even more preferably 5 μm or more and 10 μm or less.
[0037] The ratio of the thickness (μm) of the metal layer to the entire current collector (metal layer / current collector) is not particularly limited, but from the viewpoint of improving electronic conductivity and improving adhesion to the active material layer, it is preferably 1 / 16 or more and 16 / 1 or less, more preferably 1 / 8 or more and 8 / 1 or less, and even more preferably 1 / 4 or more and 4 / 1 or less.
[0038] [Active material layer] The active material layer contains an active material. The type of active material is not particularly limited, and known materials for the negative electrode and the positive electrode can be used.
[0039] The active material layer may further contain a solid electrolyte, a binder, and the like in addition to the active material, as necessary.
[0040] The thickness of the active material layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics and further suppressing warping of the first current collector from the first active material layer, it is preferably 0.1 μm or more and 100.0 μm or less, preferably 1.0 μm or more and 100.0 μm or less, and more preferably 30.0 μm or more and 100.0 μm or less.
[0041] The thickness of the active material layer is the average value of thicknesses measured at any ten points on a cross section of the active material layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).
[0042] [Solid electrolyte layer] The solid electrolyte layer contains a solid electrolyte. From the viewpoint of battery performance, the solid electrolyte preferably contains at least one solid electrolyte species selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes, and more preferably contains a sulfide solid electrolyte. As a sulfide solid electrolyte, it is preferably contained sulfur (S) as the main component of the anion element, and in addition to S, it is preferably further contained, for example, Li element and A element. The A element is at least one selected from the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. Examples of the halogen element (X) include F, Cl, Br, I, etc. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100 - x)P2S5 (70 ≦ x ≦ 80), yLiI·zLiBr·(100 - y - z)(xLi2S·(1 - x)P2S5) (0.7 ≦ x ≦ 0.8, 0 ≦ y ≦ 30, 0 ≦ z ≦ 30). The sulfide solid electrolyte may have a composition represented by the following general formula (1). Li 4-x Ge 1-x P x S4(0 < x < 1) ··· Formula (1) In Formula (1), at least a part of Ge may be substituted by at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Also, at least a part of P may be substituted by at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A part of Li may be substituted by at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A part of S may be substituted by a halogen. The halogen is at least one of F, Cl, Br, and I. As an oxide solid electrolyte, it is preferably contained oxygen (O) as the main component of the anion element, and for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of the oxide solid electrolyte include garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-P-O-based solid electrolytes, Li-B-O-based solid electrolytes, etc. Examples of the garnet-type solid electrolyte include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 Examples include etc. As perovskite-type solid electrolytes, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. can be mentioned. As NASICON-type solid electrolytes, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. can be mentioned. As Li-P-O-based solid electrolytes, Li3PO4, LIPON (a compound in which part of the O in Li3PO4 is replaced by N), and as Li-B-O-based solid electrolytes, Li3BO3, a compound in which part of the O in Li3BO3 is replaced by C, etc. can be mentioned. As a halide solid electrolyte, a solid electrolyte containing Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is suitable. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferred. Among Li 6-3z Y z X6, Li3YX6 (X represents Cl or Br) is more preferred in terms of excellent lithium ion conductivity, and further Li3YCl6 is preferred. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferably included together with a solid electrolyte such as a sulfide solid electrolyte, from the viewpoint of suppressing the oxidative decomposition of the sulfide solid electrolyte, etc.
[0043] The crystallization temperature of the solid electrolyte varies depending on the type of solid electrolyte employed. For example, it is preferably 0% or more and 90% or less, more preferably 20% or more and 85% or less, and even more preferably 50% or more and 85% or less. Note that the crystallinity of the solid electrolyte is a value measured by the X-ray diffraction method.
[0044] 〔Intermediate layer〕 The solid-state battery according to the present disclosure preferably further comprises a first intermediate layer between the first current collector and the first active material layer, the first intermediate layer comprising at least one component contained in the first active material layer and at least one component contained in the resin layer, the first intermediate layer further improving the adhesion between the first active material layer and the first resin layer. The solid-state battery according to the present disclosure preferably further comprises a second intermediate layer between the second current collector and the second active material layer, the second intermediate layer comprising at least one component contained in the second active material layer and at least one component contained in the resin layer, the second intermediate layer further improving the adhesion between the second active material layer and the second resin layer.
[0045] Hereinafter, matters common to both the first intermediate layer and the second intermediate layer will be collectively referred to simply as "intermediate layer."
[0046] From the viewpoint of enhancing the anchor effect and further improving the adhesion between the current collector and the active material layer, the intermediate layer is preferably a layer in which at least the active material contained in the active material layer and the resin contained in the resin layer are mixed.
[0047] From the viewpoint of enhancing the anchor effect and further improving the adhesion between the current collector and the active material layer, the thickness of the intermediate layer relative to the thickness of the resin layer (intermediate layer / resin layer) is preferably 1 / 30 or more and 1 / 4 or less, more preferably 1 / 20 or more and 1 / 5 or less, and even more preferably 1 / 10 or more and 1 / 6 or less.
[0048] The thickness of the intermediate layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics and enhancing the anchor effect and further improving the adhesion between the current collector and the active material layer, the thickness is preferably 0.1 μm or more and 15.0 μm or less, more preferably 0.4 μm or more and 10.0 μm or less, and even more preferably 0.6 μm or more and 8.0 μm or less.
[0049] The thickness of the intermediate layer is determined by observing a cross section of the intermediate layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and averaging the thicknesses measured at any ten points. The components contained in the intermediate layer can be confirmed by EDX analysis of the chemical composition of a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).
[0050] The method for forming the intermediate layer is not particularly limited, and examples thereof include: 1) when the resin in the resin layer is thermoplastic, a method including a step of heating a laminate in which a resin layer and an active material layer are laminated to a temperature equal to or higher than the softening temperature of the resin, and pressing the laminate; and 2) when the resin in the resin layer is thermosetting, a method of filling a precursor of a thermosetting resin and components such as an active material and a binder in the active material layer into a mold and molding by heating, etc. EXAMPLES
[0051] <Example 1> (Preparation of resin layer) A resin slurry (solid content rate 9.68% by mass, solvent: 2-ethylhexanol, solid content ratio (vinyl resin: conductive material VGCF (registered trademark)-H) = 80:20% by mass, VGCF (registered trademark)-H is manufactured by Resonac Co., Ltd.) was applied onto Ni foil (manufactured by Fukuda Metal Foil and Powder Industries Co., Ltd.) by the blade method using an applicator. This was then dried for 30 minutes on a hot plate at 170°C to form a resin layer on the Ni foil (metal layer). In this way, a current collector was obtained.
[0052] (Preparation of active material layer) 2,6-dimethyl-4-heptanone, SBR binder, solid electrolyte (Li2S-P2S5 glass ceramics), and negative electrode active material (silicon) were put into a polypropylene (PP) container, and the PP container was stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the PP container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific) and further stirred for 30 seconds with an ultrasonic dispersion device to obtain an electrode slurry. The obtained electrode slurry was applied onto the resin layer of the current collector by a blade method using an applicator. The coating film was dried on a hot plate at 170 ° C. for 30 minutes, and a negative electrode active material layer was formed on the resin layer on the metal layer (Ni foil), and an electrode test piece (negative electrode active material layer / resin layer / Ni foil) of Example 1 was obtained.
[0053] <Comparative Example 1> An electrode test piece for Comparative Example 1 was obtained under the same specifications as those of Example 1, except that the resin slurry did not contain the conductive material VGCF (registered trademark)-H.
[0054] <Comparative Example 2> An electrode test piece for Comparative Example 2 was obtained in the same manner as in Example 1, except that no resin layer was provided on the metal layer, and the negative electrode active material layer was formed directly on the metal layer.
[0055] <Evaluation of electronic conductivity> For each electrode specimen, a four-terminal probe was applied at 5 cm intervals to the surface on the metal layer side and the surface opposite to the metal layer, i.e., the surface on the active material layer side, to measure the surface resistance. The results are shown in 1.
[0056] <Evaluation of adhesion between current collector and active material layer> The electrode test pieces of each example were cut to 20 mm x 80 mm, roll-press molded under conditions of a linear pressure of 1.5 kN / cm and a temperature of 25°C, and then subjected to a T-peel test using a tensile tester to measure the peel strength. In addition, it was evaluated by visual observation whether the current collector had peeled off from the active material layer. The results are shown in Table 1. In the table, a higher peel strength value indicates a higher adhesion between the current collector and the active material layer.
[0057] [Table 1]
[0058] As shown in Table 1, it was found that the electrode test pieces of the Examples were superior to the electrode test pieces of the Comparative Examples in both adhesion between the active material layer and the current collector and in electronic conductivity. [Explanation of symbols]
[0059] 20 First solid electrolyte layer 30 Second solid electrolyte layer A Negative electrode active material layer (first active material layer) B Solid electrolyte layer C Positive electrode active material layer (second active material layer) 101 Negative electrode active material 102 Solid electrolyte 103 Cathode active material 105, 107 Conductive additives 109, 111 Binder 113 Negative electrode current collector (first current collector) 115 Positive electrode current collector (second current collector)
Claims
1. a first current collector including a first resin layer containing a resin and a conductive material and a first metal layer; a first active material layer; solid electrolyte layer, A second active material layer, and a second current collector including a second resin layer containing a resin and a conductive material and a second metal layer; are layered in this order, a first resin layer provided on the first current collector on a side of the first active material layer, and a second resin layer provided on the second current collector on a side of the second active material layer.
2. a first intermediate layer between the first current collector and the first active material layer, in which at least one component contained in the first active material layer and at least one component contained in the resin layer are mixed; 2. The solid-state battery according to claim 1, further comprising a second intermediate layer between the second current collector and the second active material layer, the second intermediate layer including at least one component contained in the second active material layer and at least one component contained in the resin layer.
3. the first current collector has a three-layer structure in which the first resin layer, the first metal layer, and the first resin layer are laminated in this order from the first active material layer side, 3. The solid-state battery according to claim 1, wherein the second current collector has a three-layer structure in which the second resin layer, the second metal layer, and the second resin layer are laminated in this order from the second active material layer side.
Citation Information
Patent Citations
Positive electrode for lithium secondary battery and lithium secondary battery using the same
JP1999312516A
Multilayer battery
JP2004179091A
Electrode for all-solid-state lithium ion battery, all-solid-state lithium ion battery, and method of manufacturing all-solid-state lithium ion battery
JP2014093156A
Lithium solid battery
JP2021152989A
Electrode plate, electrochemical device, and apparatus
US20220037669A1